Fractal scaling exponents of heart rate variability association with linear indices and Poincaré Plot - Cardoso, Marco A. [UNESP]; Dos Santos, Marcio Antonio [UNESP]; Abreu, Luiz Carlos de; Fontes, Anne Michelli G. [UNESP]; Silva, Ariany Garcia da [UNESP]; Ogata, Cristiane Mayumi [UNESP]; Oliveira, Letícia Santana de [UNESP]; Sousa, Fernando Henrique [UNESP]; Amaral, Joice Anaize Tonon do [UNESP]; Cano, Amanda de Souza [UNESP]; Plassa, Bruna O. [UNESP]; Milan, Réveni [UNESP]; et al. (My University, 2014)
The literature indicated that the fractal analysis of heart rate variability (HRV) is related to the chaos theory. However, it is not clear if the both short and long-term fractal scaling exponents of HRV are reliable for short period analysis in women. We evaluated the association of the fractal exponents of HRV with the time and frequency domain and geometric indices of HRV. We evaluated 65 healthy women between 18 and 30 years old. HRV was analyzed with a minimal number of 256 RR intervals in the time (SDNN, RMSSD, NN50 and pNN50) and frequency (LF, HF and LF/HF ratio) domains, the geometric index were also analyzed (triangular indexRRtri, triangular interpolation of RR intervals-TINN and Poincaré plot-SD1, SD2 and SD1/SD2) as well as short and long-term fractal exponents (alpha-1 and alpha-2) of the detrended fluctuation analysis (DFA). No significant correlation was observed for alpha-2 exponent with all indices. There was significant correlation of the alpha-1 exponent with RMSSD, pNN50, SDNN/RMSSD, LF (nu), HF (nu and ms2 ), LF/HF ratio, SD1 and SD1/SD2 ratio. Our data does not indicate the alpha-2 exponent to be used for 256 RR intervals and we support the alpha-1 exponent to be used for HRV analysis in this condition.